Palmar main line polymorphisms in cataracts. Issue 660 (October 1980) - Padma, T.; Murty, J. S.
Abstract : The palm prints of patients with different types of cataract (total, nuclear, zonular, cortical and complicated) were analysed for main line terminations and compared with those of a random population. The cases were also grouped into congenital, juvenile and senile types for broader comparison. The results showed significant variations for all the 4 main line terminations (D, C, B and A) in senile and cortical cataracts, while among other types of cataract, congenital cases differed significantly in D and A line, zonular in C and A line and nuclear in B and A line terminations compared with controls. A comparison of familial and isolated cases revealed significant differences for D and A line terminations only in cases of senile cataract. The main line terminations also indicated considerable sex-dependent heterogeneity among the diseased and control subjects. The significance of the results obtained are discussed in terms of pleiotropic mechanisms leading to the formation of cataract.